An advanced radiometric calibration approach for uncooled thermal cameras. (13th December 2017) - Lin, Dong; Maas, Hans‐Gerd; Westfeld, Patrick; Budzier, Helmut; Gerlach, Gerald
Abstract: Uncooled thermal cameras are increasingly used in thermography applications due to their lower cost and size. However, there are two significant limiting constraints which must be taken into consideration in a radiometric calibration before the actual application: (i) temporal non‐uniformity (a temperature‐dependent drift problem); and (ii) spatial non‐uniformity (fixed‐pattern noise – FPN). Conventional temporal non‐uniformity corrections (NUC) take advantage of an internal reference source but such methods are not valid for sequential images when the focal‐plane array (FPA) temperature is changing rapidly. A novel shutterless correction method is proposed to stabilise the camera's response. Moreover, instead of implementing the spatial NUC first, multi‐point correction is leveraged to remove FPN after the temporal NUC. Finally, a Planck curve is applied to convert thermal image values into object temperatures. Experimental results show that the proposed method is more effective for images with rapidly changing FPA temperatures than conventional shutterless methods and traditional shutter‐based methods.